Орибатиды родов Phthiracarus и Archiphthiracarus (Oribatei, Phthiracaridae) на Украине. Сообщение I - Сергиенко, Г.Д. (Вестник зоологии, 1987)
Типы описываемых в статье новых видов и материал, по которому составлено переописание Phthiracarus italicus и Ph. laevigatus, хранятся в Институте зоологии им. И. И. Шмальгаузена АН УССР (Киев). The paper contains irformation relating four Phthiracarid species, two of which are described as new: Phthiracarus conformis sp. n. and Archiphthiracarus pilosus sp. n. Type material is deposited in the Schmalhausen Institute of Zoology (Kiev).